Copper-based diatomic catalyst as well as preparation method and application thereof
By using specific atmosphere and high-temperature calcination technology to form a copper-based diatom catalyst in the preparation of catalyst, the problem of insufficient catalyst activity and selectivity is solved, and the efficient production of propylene oxide is achieved, linear constraints are broken, and excellent catalytic activity and Environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411414486.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing catalysts have insufficient conversion and selectivity in catalyzing the direct gas-phase epoxidation reaction between propylene and oxygen, resulting in low production efficiency of propylene oxide, and traditional processes have problems of environmental pollution and high separation costs.
By pretreating the metal salt solution in a specific atmosphere, the intercalation and special structure of the two-dimensional support are promoted, and the coordination anchoring of the highly ordered diatomic active center and the nitrogen-containing support are formed, and the copper-based diatomic catalyst is prepared. High-temperature roasting and procedural cooling and annealing technology ensure pairwise dispersion and synergistic effects of copper diatomic sites.
It achieves high catalytic activity, high selectivity and generation rate of propylene oxide, breaks the linear constraints in selective oxidation reactions, has excellent catalytic activity and target product selectivity, and is simple in the process, green and environmentally friendly, suitable for industrial production.
Smart Images

Figure CN119303611A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, and in particular to a copper-based diatomic catalyst and a preparation method and application thereof. Background Art
[0002] Propylene oxide (PO) is an important chemical raw material with the third largest output among propylene derivatives. It is mainly used to synthesize various high-value chemicals, such as propylene glycol, polypropylene alcohol, polyurethane and propylene carbonate. At present, the traditional production processes of PO include the chlorohydrin method and the co-oxidation method. However, the chlorohydrin method consumes a large amount of water resources, and chlorinated wastewater is prone to cause environmental pollution. The PO synthesized by this process also contains chlorine and cannot be applied to the processing and production of electronic chemicals. The co-oxidation method uses ethylbenzene or isobutylene to co-oxidize propylene. Although it can obtain PO with higher purity, the output of by-products styrene and tert-butyl alcohol is too large, and the separation cost is high.
[0003] In recent years, the direct epoxidation of propylene (DEP) with molecular oxygen as the oxidant has the advantages of high atomic utilization, simple and environmentally friendly synthesis route, relatively safe process and low raw material cost, and is considered to be the most ideal technical route. Related studies have shown that common DEP reaction catalysts are mainly Ag-based and Cu-based oxide catalysts. Among them, the raw materials of Cu-based oxide catalysts are cheap and easy to obtain, and the metal valence state is rich, which has attracted the attention of scientific research and industry. However, since the allylic hydrogen of propylene in the DEP reaction is very active, it has been reported that the catalyst usually causes propylene and oxygen to be easily co-adsorbed on the catalyst surface, and activates oxygen into nucleophilic lattice oxygen species, thereby causing deep oxidation of propylene, making it impossible to increase the conversion rate and selectivity of the reaction simultaneously, which has a "seesaw effect". Although catalysts with atomically dispersed active sites (such as CN115475645A) solve the problems of many byproducts and poor selectivity of the above copper-based oxide catalysts, their highly dispersed and disordered active sites have limited activation ability for reaction intermediates, which is not conducive to the efficient generation of key intermediates (such as oxygen heterometallic rings), further resulting in unsatisfactory catalytic activity and conversion rate. Therefore, catalysts are the bottleneck for opening up the DEP reaction process route.
[0004] Therefore, it is of great significance to design a catalyst with high catalytic activity, high PO selectivity and generation rate for catalyzing the direct gas-phase epoxidation reaction of propylene with oxygen to prepare propylene oxide. Summary of the invention
[0005] In view of the above problems, the present invention aims to provide a catalyst having high catalytic activity, high PO selectivity and generation rate for catalyzing the direct gas-phase epoxidation reaction of propylene with oxygen to prepare propylene oxide, as well as a preparation method and application thereof.
[0006] In the first aspect, the present invention provides a catalyst and a preparation method thereof, which is characterized in that a precursor solution is placed in a specific atmosphere for pretreatment, inducing a metal salt solution to intercalate a two-dimensional carrier and promoting the in-situ generation of a special structure of the carrier, so that the diatomic active center forms a highly ordered coordination anchor with the nitrogen-containing carrier, and specifically comprises the following steps:
[0007] A method for preparing a catalyst comprises the following steps:
[0008] (1) in an atmosphere containing carbon dioxide, melamine, a metal salt and a solvent are mixed and stirred for prepolymerization to obtain a suspension A; or in an atmosphere containing carbon dioxide, melamine, a metal salt, an amino acid and a solvent are mixed and stirred for prepolymerization to obtain a suspension A;
[0009] (2) reacting the suspension A obtained in step (1) at a certain temperature to obtain a solid product, and washing and drying the obtained solid product to obtain a mixture B;
[0010] (3) Calcination: The mixture B obtained in step (2) is annealed to obtain the catalyst.
[0011] In some embodiments, the amino acid comprises at least one of L-cysteine, glycine and D-phenylalanine. In some preferred embodiments, the amino acid is L-cysteine.
[0012] In some embodiments, the stirring speed of step (1) is 500 rpm to 1000 rpm. In some embodiments, the stirring speed of step (1) is 500 rpm to 900 rpm. In some embodiments, the stirring speed of step (1) is 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm.
[0013] In some embodiments, the stirring time of step (1) is 12h-36h. In some embodiments, the stirring time of step (1) is 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h or 36h.
[0014] In some embodiments, the stirring in step (1) is carried out at 0° C. to 60° C. In some embodiments, the stirring in step (1) is carried out at 0° C., 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., or 60° C.
[0015] In some embodiments, the carbon dioxide-containing atmosphere is a pure carbon dioxide atmosphere. In some embodiments, the carbon dioxide-containing atmosphere is a gas atmosphere with a carbon dioxide purity of ≥ 99% vol. In some embodiments, the carbon dioxide-containing atmosphere is a gas atmosphere with a carbon dioxide purity of ≥ 99.99% vol.
[0016] In some embodiments, the carbon dioxide-containing atmosphere is a mixed gas of carbon dioxide and other gases, wherein the other gases are selected from at least one of nitrogen, argon, oxygen or air.
[0017] In some embodiments, the atmosphere is a mixture of carbon dioxide and other gases, the volume ratio of carbon dioxide to other gases is ≥5:1; the other gases are selected from at least one of nitrogen, argon, oxygen or air. In some embodiments, the atmosphere is a mixture of carbon dioxide and other gases, the volume ratio of carbon dioxide to other gases is ≥5:1; the other gases are selected from nitrogen.
[0018] In some embodiments, the metal salt is selected from at least one of cupric chloride, cupric chloride hydrate, cuprous chloride, cupric nitrate, cupric acetate, or copper nitride.
[0019] In some embodiments, the copper chloride hydrate includes at least one of copper chloride monohydrate, copper chloride dihydrate, copper chloride trihydrate, or copper chloride tetrahydrate.
[0020] In some embodiments, the solvent is a mixed solvent of water and ethanol.
[0021] In some embodiments, the solvent is a mixed solvent of water and ethanol, and the volume ratio of water to ethanol in the solvent is 1.0:0.8-1.0:1.5. In some embodiments, the solvent is a mixed solvent of water and ethanol, and the volume ratio of water to ethanol in the solvent is 1.0:0.8, 1.0:0.9, 1.0:1.0, 1.0:1.1, 1.0:1.2, 1.0:1.3, 1.0:1.4 or 1.0:1.5.
[0022] In some embodiments, the certain temperature in step (2) is 150° C.-240° C. In some embodiments, the certain temperature in step (2) is 150° C., 160° C., 170° C., 175° C., 180° C., 185° C., 190° C., 200° C., 210° C., 220° C., 230° C. or 240° C.
[0023] In some embodiments, the reaction time of the reaction in step (2) is 2h-8h. In some embodiments, the reaction time of the reaction in step (2) is 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0024] In some embodiments, the washing is washing with water and ethanol in sequence.
[0025] In some embodiments, the drying is performed at 60° C. to 80° C. In some embodiments, the drying is performed at 60° C., 65° C., 70° C., 75° C. or 80° C.
[0026] In some embodiments, the calcination temperature of the calcination in step (3) is 300° C. to 650° C. In some embodiments, the calcination temperature of the calcination in step (3) is 300° C., 400° C., 500° C., 510° C., 520° C., 530° C., 540° C., 550° C., 560° C., 570° C., 580° C., 590° C., 600° C., or 650° C.
[0027] In some embodiments, the calcination time in step (3) is 2h-8h. In some embodiments, the calcination time in step (3) is 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0028] In some embodiments, the heating rate of the calcination in step (3) is 2°C / min to 8°C / min. In some embodiments, the heating rate of the calcination in step (3) is 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min.
[0029] In some embodiments, the calcination in step (3) is performed in a nitrogen or argon atmosphere.
[0030] In some embodiments, the calcination in step (3) is carried out in a mixed gas atmosphere of hydrogen and argon; the volume ratio of hydrogen to argon in the mixed gas is 10:90-1:99. In some embodiments, the calcination in step (3) is carried out in a mixed gas atmosphere of hydrogen and argon; the volume ratio of hydrogen to argon in the mixed gas is 10:90, 9:91, 8:92, 7:93, 6:94, 5:95, 4:96, 3:97, 2:98, 1:99. In some embodiments, the calcination in step (3) is carried out in a mixed gas atmosphere of hydrogen and argon; the volume ratio of hydrogen to argon in the mixed gas is 5:95.
[0031] In some embodiments, the annealing is performed by programmed temperature reduction.
[0032] In some embodiments, the programmed cooling is cooling at a rate of 0.5°C / min-5.0°C / min. In some embodiments, the programmed cooling is cooling at a rate of 0.5°C / min, 1.0°C / min, 1.5°C / min, 2.0°C / min, 2.5°C / min, 3.0°C / min, 4.0°C / min or 5.0°C / min. In some preferred embodiments, the programmed cooling is cooling at a rate of 2.0°C / min.
[0033] In some embodiments, the annealing is annealing to 20° C.-30° C. In some embodiments, the annealing is annealing to 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., or 30° C.
[0034] In a second aspect, the present invention provides a catalyst prepared according to the aforementioned preparation method.
[0035] A catalyst is prepared by the preparation method described in the first aspect.
[0036] In a third aspect, the present invention provides an application of the catalyst described in the second aspect.
[0037] A use of the catalyst described in the second aspect in catalyzing the gas-phase direct epoxidation reaction of propylene to prepare propylene oxide.
[0038] The diatomic active center formed by the catalyst provided by the present invention has a synergistic effect in the catalytic process, follows the "Sabatier principle", breaks the linear constraint relationship in the selective oxidation reaction, and optimizes its activity while maintaining a high main product selectivity.
[0039] In a fourth aspect, the present invention provides a method for preparing propylene oxide.
[0040] A method for preparing propylene oxide comprises: in the presence of the catalyst described in the second aspect, propylene and oxygen undergo gas phase epoxidation reaction to obtain propylene oxide.
[0041] In some embodiments, a method for preparing propylene oxide comprises: in the presence of the catalyst of claim 6, the propylene and oxygen are diluted with nitrogen and then subjected to a gas phase epoxidation reaction to obtain propylene oxide.
[0042] In some embodiments, the volume ratio of propylene to oxygen is 1: 1 to 5: 1. In some embodiments, the volume ratio of propylene to oxygen is 1: 1, 2: 1, 3: 1, 4: 1 or 5: 1. In some preferred embodiments, the volume ratio of propylene to oxygen is 2: 1.
[0043] In some embodiments, the volume ratio of propylene to nitrogen is 1:10 to 1:20. In some embodiments, the volume ratio of propylene to nitrogen is 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.
[0044] In some embodiments, 25 mg to 200 mg of the catalyst is added per 1 L of propylene in the gas phase epoxidation reaction. In some embodiments, 25 mg, 50 mg, 60 mg, 70 mg, 80 mg, 90 mg, 100 mg, 110 mg, 120 mg, 130 mg, 140 mg, 150 mg, 160 mg, 170 mg, 180 mg, 190 mg or 200 mg of the catalyst is added per 1 L of propylene in the gas phase epoxidation reaction.
[0045] In some embodiments, the reaction temperature of the gas phase epoxidation reaction is 200° C. to 350° C. In some embodiments, the reaction temperature of the gas phase epoxidation reaction is 200° C., 210° C., 220° C., 230° C., 240° C., 250° C., 260° C., 270° C., 280° C., 290° C., 300° C., 310° C., 320° C., 330° C., 340° C., or 350° C.
[0046] In some embodiments, the particle size of the catalyst is ≤300 μm. In some embodiments, the particle size of the catalyst is ≤250 μm. In some embodiments, the particle size of the catalyst is 50 μm to 300 μm. In some embodiments, the particle size of the catalyst is 50 μm, 70 μm, 90 μm, 100 μm, 110 μm, 120 μm, 150 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm or 300 μm.
[0047] In a fifth aspect, the present invention provides another method for preparing propylene oxide.
[0048] A method for preparing propylene oxide comprises: performing gas-phase epoxidation reaction of propylene and oxygen with nitrogen as carrier gas in a fixed bed reactor filled with the catalyst of the second aspect to obtain propylene oxide.
[0049] In some embodiments, the volume ratio of propylene to oxygen is 1: 1 to 5: 1. In some embodiments, the volume ratio of propylene to oxygen is 1: 1, 2: 1, 3: 1, 4: 1 or 5: 1. In some preferred embodiments, the volume ratio of propylene to oxygen is 2: 1.
[0050] In some embodiments, the volume ratio of propylene to nitrogen is 1:10 to 1:20. In some embodiments, the volume ratio of propylene to nitrogen is 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.
[0051] In some embodiments, the space velocity of the gas phase epoxidation reaction is 6000ml / g / h-40000ml / g / h. In some embodiments, the space velocity of the gas phase epoxidation reaction is 6000ml / g / h, 10000ml / g / h, 15000ml / g / h, 16000ml / g / h, 17000ml / g / h, 18000ml / g / h, 19000ml / g / h, 20000ml / g / h, 25000ml / g / h, 30000ml / g / h, 35000ml / g / h or 40000ml / g / h.
[0052] In some embodiments, the reaction temperature of the gas phase epoxidation reaction is 200° C. to 350° C. In some embodiments, the reaction temperature of the gas phase epoxidation reaction is 200° C., 210° C., 220° C., 230° C., 240° C., 250° C., 260° C., 270° C., 280° C., 285° C., 290° C., 300° C., 310° C., 320° C., 330° C., 340° C., or 350° C.
[0053] In some embodiments, the particle size of the catalyst is ≤300 μm. In some embodiments, the particle size of the catalyst is ≤250 μm. In some embodiments, the particle size of the catalyst is 50 μm to 300 μm. In some embodiments, the particle size of the catalyst is 50 μm, 70 μm, 90 μm, 100 μm, 110 μm, 120 μm, 150 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm or 300 μm. Beneficial Effects
[0054] Compared with the prior art, a certain embodiment of the present invention has at least one of the following beneficial effects:
[0055] (1) The present invention induces metal ions in the prepolymer solution through a specific atmosphere, so that the metal ions are intercalated into the two-dimensional carbon nitride carrier material, and after subsequent high-temperature calcination and programmed temperature reduction annealing, the metal ions are anchored in pairs on the carbon nitride nanosheets in the form of Cu-N coordination, thereby preparing a copper-based diatomic catalyst;
[0056] (2) Compared with traditional single-atom or nanocluster catalysts, the catalyst designed by the present invention has metal centers dispersed in pairs at the atomic level on the carrier, and the interaction between the diatomic active centers has unique advantages in regulating the electronic structure;
[0057] (3) The catalyst of the present invention follows the "Sabatier principle", and there is a synergistic effect between the copper diatomic sites, breaking the linear constraint relationship in the selective oxidation reaction, and has excellent catalytic activity and target product selectivity;
[0058] (4) The catalyst of the present invention has simple synthesis conditions, short production cycle, high metal utilization rate, mild catalytic reaction conditions, green and environmentally friendly, simple and easy to build equipment, and is convenient for industrial production.
[0059] (5) In the preparation method of the catalyst of the present invention, step (1) is preferably carried out under a CO2 atmosphere with a purity higher than 95%, which is beneficial to improving the activity of the obtained catalyst and is beneficial to improving the propylene conversion rate, PO selectivity and PO formation rate of the obtained catalyst in the direct gas-phase epoxidation reaction of propylene.
[0060] (6) The present invention preferably uses L-cysteine as the amino acid added in step (1), which is beneficial to improving the activity of the obtained catalyst, and is beneficial to improving the propylene conversion rate, PO selectivity and PO formation rate of the obtained catalyst in the direct gas-phase epoxidation reaction of propylene.
[0061] (7) In the preparation method of the catalyst of the present invention, the reaction in step (1) is preferably carried out under a CO2 atmosphere with a purity higher than 95%, and L-cysteine is added in step (1). The two have an unexpected synergistic technical effect, which is beneficial to improving the propylene conversion rate, PO selectivity and PO formation rate of the obtained catalyst in the direct gas-phase epoxidation reaction of propylene.
[0062] (8) In step (3) of the present invention, preferably a programmed cooling rate of 2.0°C / min is used for annealing and cooling. The resulting catalyst has unexpectedly high propylene conversion, high PO selectivity and high PO formation rate in the direct gas-phase epoxidation reaction of propylene.
[0063] (9) Compared with other catalysts in the prior art, the catalyst provided by the present invention has unexpectedly excellent propylene conversion, PO selectivity and PO formation rate in the direct gas-phase epoxidation reaction of propylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 TEM spectrum (transmission (TEM) electron diffraction pattern, Figure a) and ACHAADF-STEM pattern (spherical aberration corrected scanning transmission electron microscope pattern, Figure b) of the copper-based diatomic catalyst in Example 1;
[0065] Figure 2 is the AC HAADF-STEM image of the supported copper-based catalyst in Comparative Example 1;
[0066] Figure 3 It is the AC HAADF-STEM image of the supported copper-based catalyst in Comparative Example 2;
[0067] Figure 4 XRD spectra (X-ray diffraction spectra) of the copper-based catalysts in Examples 1 to 2 and Comparative Examples 1 to 5;
[0068] Figure 5 It is the FTIR spectra (Fourier infrared spectra) of the copper-based catalysts in Examples 1 to 2 and Comparative Examples 1 to 5.
[0069] Terminology
[0070] In the description of the present invention, “plurality” means two or more than two, unless otherwise clearly and specifically defined.
[0071] The term "room temperature" means ambient temperature, referring to a temperature between about 10°C and about 30°C, or between about 20°C and 30°C, or about 25°C.
[0072] The term "wt%" means percent by mass.
[0073] The unit "ml / g / h" of the term "space velocity" represents the volume of gas introduced per 1 g of catalyst per hour.
[0074] The terms "ml" and "mL" have the same meaning and both mean milliliters.
[0075] The term "V / V / V" or "V / V" means a volume ratio.
[0076] The term "mmol g" in the present invention cat -1 h -1 " represents the amount of product produced per gram of catalyst per hour (in millimoles).
[0077] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0078] In the following, all numbers disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% will be explicitly disclosed, where "+ / -" means plus or minus. DETAILED DESCRIPTION
[0079] In order to enable those skilled in the art to better understand the technical solution of the present invention, some non-limiting embodiments are further disclosed below to further describe the present invention in detail.
[0080] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.
[0081] Example 1: Preparation of Catalyst
[0082] 1. Preparation method of catalyst:
[0083] (1) melamine, cupric chloride and L-cysteine are mixed, deionized water and anhydrous ethanol are added, CO2 is continuously introduced, a high-purity CO2 (CO2 content 99.99% vol) atmosphere is maintained in a closed reaction vessel, and the mixture is stirred at 800 rpm for 20 h at 50° C. to form a uniform blue-green suspension; the mass ratio of melamine, cupric chloride, L-cysteine, deionized water and anhydrous ethanol is 5.000:1.550:0.035:50.000:40.000;
[0084] (2) reacting the above solution at 200°C for 3 h, adding 150 mL of deionized water and 150 mL of anhydrous ethanol respectively to wash the obtained solid product, and drying it in an oven at 60°C for 12 h;
[0085] (3) The mixture was placed in a sealed corundum boat, heated to 550°C in an Ar atmosphere in a tube furnace at a heating rate of 5°C / min and calcined for 4 h. The catalyst was then annealed at room temperature (25°C) at a rate of 2.0°C / min to obtain the catalyst.
[0086] 2. Transmission electron microscopy and spherical aberration high-resolution transmission electron microscopy: The obtained catalyst was tested by transmission electron microscopy and spherical aberration high-resolution transmission electron microscopy. The results are shown in Figure 1 , are transmission electron microscopy and spherical aberration high-resolution transmission electron microscopy images of the copper-based diatomic catalyst prepared in Example 1. It can be seen from the figure that the catalyst prepared in this example presents a two-dimensional sheet structure with curled edges, and the copper species supported on the surface of the carbon nitride support has obvious diatomic characteristics.
[0087] Example 2
[0088] (1) Melamine, cupric chloride and L-cysteine are mixed, deionized water and anhydrous ethanol are added, and CO2 is continuously introduced to maintain a high-purity CO2 (CO2 content 99.99% vol) atmosphere in a closed reaction container, and stirred at 60° C. and 800 rpm for 20 h to form a uniform blue-green suspension; the mass ratio of melamine, cupric chloride, L-cysteine, deionized water and anhydrous ethanol is 5.000:2.350:0.0035:50.000:40.000.
[0089] (2) reacting the above solution at 180° for 4 h, adding 150 mL of deionized water and 150 mL of anhydrous ethanol to wash the obtained solid product, and drying it in an oven at 60°C for 12 h;
[0090] (3) The above mixture was placed in a sealed corundum porcelain boat, heated to 550°C in a tube furnace in a 5% H2 / 95% Ar atmosphere at a heating rate of 8°C / min and calcined for 3 h. The catalyst was obtained after annealing at room temperature (25°C) at a programmed temperature of 2.0°C / min.
[0091] Comparative Example 1: Catalyst prepared without CO2 protection and without adding amino acid
[0092] 1. Preparation of catalyst: Compared with the operation of Example 1, the difference of Comparative Example 1 is that L-cysteine is not added and CO2 is not introduced (i.e., under air atmosphere conditions); the remaining operations are the same as those of Example 1 to obtain a catalyst.
[0093] 2. Spherical aberration high-resolution transmission electron microscopy detection: The catalyst prepared in Comparative Example 1 was subjected to spherical aberration high-resolution transmission electron microscopy detection. The results are shown in Figure 2 , which is a spherical aberration high-resolution transmission electron microscope image of the catalyst prepared in Comparative Example 1. As can be seen from the figure, the copper species supported on the surface of the carbon nitride support in the catalyst prepared in this comparative example exhibits atomic aggregation characteristics, indicating that small particle clusters are formed.
[0094] Comparative Example 2: Catalyst prepared without programmed cooling
[0095] 1. Preparation of catalyst: Compared with the operation of Example 1, the difference is that the catalyst is not subjected to programmed cooling after calcination (ie, natural cooling at room temperature), and the remaining operations are the same as those of Example 1 to obtain the catalyst.
[0096] 2. Spherical aberration high-resolution transmission electron microscopy detection: The catalyst prepared in Comparative Example 2 was subjected to spherical aberration high-resolution transmission electron microscopy detection. The results are shown in Figure 3 , is a spherical aberration high-resolution transmission electron microscope image of the supported catalyst prepared in Comparative Example 2. It can be seen from the figure that the copper species in the catalyst prepared in this example is supported on the surface of the carbon nitride support in the form of single-atom dispersion.
[0097] Comparative Example 3: No amino acid added
[0098] Preparation of catalyst: Compared with the operation of Example 1, the difference of Comparative Example 3 is that L-cysteine is not added; the remaining operations are the same as those of Example 1 to obtain a catalyst.
[0099] Conclusion: If L-cysteine is not added or CO2 gas is not introduced during the catalyst synthesis process, the copper species in the catalyst will agglomerate or oxidize to form cuprous oxide or elemental copper; the introduction of CO2 atmosphere during the catalyst synthesis process and programmed cooling after high-temperature calcination are beneficial to prevent the copper loaded on the surface of the carbon nitride support from agglomeration and oxidation.
[0100] Comparative Example 4: Investigation of catalysts in the prior art
[0101] (1) 0.5 g of copper chloride dihydrate, 0.5 g of 2,2-bipyridine and 0.2 g of oxalic acid were added to a mixed solution consisting of 60 mL of deionized water and 10 mL of methanol, stirred at room temperature for 1 h and then centrifuged to obtain a light blue solid;
[0102] (2) 20 g of melamine was placed in an alumina crucible, heated to 550°C at a rate of 20°C / min in a muffle furnace, maintained for 2 h, cooled, and then repeatedly heated to 500°C at a rate of 5°C / min, maintained for 3 h, to obtain a light yellow powder;
[0103] (3) 0.5 g of light yellow powder and 50 mg of light blue solid were added to 50 mL of methanol and stirred at room temperature for 24 h. The obtained solid was heated to 250 °C in a muffle furnace at a rate of 2 °C / min and maintained for 10 h to obtain a supported copper-based catalyst.
[0104] Reference: Nat. Commun. 2022, DOI: 10.1038 / s41467-022-28987-1
[0105] Comparative Example 5: Investigation of catalysts in the prior art
[0106] (1) 20 g of melamine was placed in an alumina crucible, and the temperature was raised to 550° C. at a rate of 20° C. / min in a muffle furnace, and maintained for 2 h. After cooling, the temperature was repeatedly raised to 500° C. at a rate of 5° C. / min, and maintained for 3 h to obtain a light yellow carbon nitride powder;
[0107] (2) 0.64 g of copper chloride and 0.7 g of carbon nitride powder were added to 200 mL of formamide, and the mixture was ultrasonically dispersed for 10 min and then stirred in an oil bath at 120 °C for 12 h. 150 mL of deionized water and 150 mL of anhydrous ethanol were added to wash the obtained solid product, and the solid product was dried in an oven at 60 °C overnight.
[0108] (3) The mixture was placed in a sealed corundum boat, heated to 500° C. in a tube furnace in a N 2 atmosphere at a heating rate of 2° C. / min and calcined for 5 h to obtain a supported copper-based catalyst after annealing.
[0109] Reference: Nature 2023, Doi:10.1038 / s41586-023-06529-z
[0110] Example 3: X-ray diffraction analysis, Fourier transform infrared spectroscopy analysis
[0111] 1. X-ray diffraction analysis
[0112] Operation: X-ray diffraction analysis was performed on the above catalysts. The specific operation is as follows: The phase structure of the sample was recorded on a Rigaku Ultima IV X-ray diffractometer. Test conditions: Cu Kα radiation source was used Scanning range 5-60°, voltage 35kV, current 15mA, scanning speed 10°min-1 n. Test results such as Figure 4 shown.
[0113] Result analysis: It can be seen from the figure that the catalysts obtained in Examples 1 to 2, Comparative Example 2, and Comparative Example 4 to 5 only detected the XRD characteristic diffraction peak belonging to the (002) crystal plane of carbon nitride (2θ=27.7°, JCPDS:87-1526), indicating that the copper species in the catalysts prepared in Examples 1 to 2, Comparative Example 2, and Comparative Example 4 to 5 were loaded on the surface of the carbon nitride carrier without forming the copper element (2θ=43.3°: (111) crystal plane, 2θ=50.4°: (200) crystal plane, 2θ=74.1°: (220) crystal plane, JCPDS: 04-0836), cuprous oxide (2θ = 43.3°: (110) crystal plane, 2θ = 61.5°: (111) crystal plane, 2θ = 73.0°: (200) crystal plane, JCPDS: 05-0667) and cupric oxide (2θ = 32.7°: (110) crystal plane, 2θ = 35.6°: (111) crystal plane, 2θ = 38.7°: (020) crystal plane, 2θ = 48.8°: (002) crystal plane, JCPDS: 48-1548) and other crystal phases, indicating that no agglomeration and oxidation occurred. In contrast, the catalyst prepared in Comparative Example 3 also has a crystal phase of cuprous oxide, and the catalyst prepared in Comparative Example 1 also has a crystal phase of elemental copper.
[0114] 2. Fourier infrared spectroscopy analysis
[0115] Operation: Fourier transform infrared spectroscopy analysis was performed on the above catalysts. The specific operation is as follows: Fourier transform infrared spectrometer (Nicolet N6700) was used to analyze the functional groups on the sample surface. Test conditions: 32 scans, scanning range 4000-400 cm -1 , resolution 4cm -1 Before the test, weigh a small amount of catalyst and potassium bromide sample, mix them thoroughly and grind them evenly, use a mold to press the mixed powder of the sample into tablets, and test it after drying for 15 minutes. The test results are as follows Figure 5 shown.
[0116] Results analysis: As can be seen from the figure, all samples showed typical FT-IR spectroscopic characteristics of carbon nitride materials, among which 800cm -1 、890cm -1 、1200cm -1 ~1650cm -1 and 3165cm -1The infrared characteristic peaks appearing at 2188 cm-1 correspond to the out-of-plane bending vibration peak of the s-triazine ring of the carbon nitride material, the stretching vibration peak of the aromatic C-N heterocyclic ring and the stretching vibration peak of the -NH2 group. -1 A characteristic peak belonging to the cyanide functional group (–C≡N) appeared at the carbon nitride support, indicating that the introduction of CO2 gas during the catalyst synthesis process can induce the in situ formation of cyanate ions, which enter the interlayer of carbon nitride together with copper ions, prompting the bulk carbon nitride to be exfoliated into nanosheets and forming cyanide defects on the surface of the carbon nitride nanosheets, leading to the coordination anchoring of copper diatoms on the carbon nitride support.
[0117] Conclusion: The introduction of CO2 gas during the catalyst synthesis process (see Examples 1 to 2, Comparative Examples 2 to 3) is beneficial to the intercalation of copper ions with the in-situ formed cyanate on the carbon nitride support, and the formation of cyanide defects on the surface of the carbon nitride nanosheets, which induces the coordination anchoring of copper diatoms on the carbon nitride support after subsequent high-temperature calcination and programmed annealing cooling.
[0118] Comparative Examples 6-10, Example 4: Investigation of Gas Atmosphere
[0119] The gas atmosphere was investigated based on the operation of Example 1, that is, the high-purity CO2 in Example 1 was replaced with the gas described in Table 1, and the remaining operations were the same as Example 1.
[0120] Table 1: Investigation of gas atmosphere
[0121] Comparative Example Gas Comparative Example 6 Nitrogen Comparative Example 7 Argon Comparative Example 8 Air Comparative Example 9 <![CDATA[CO2:N2=1:1(V / V)]]> Comparative Example 10 <![CDATA[CO2:N2=2:1(V / V)]]> Example 4 <![CDATA[CO2:N2=5:1(V / V)]]>
[0122] Comparative Examples 11-15: Investigation of the programmed cooling rate of the annealing step
[0123] The programmed cooling rate of the annealing step is performed based on the operation of Example 1, that is, the programmed cooling rate of 2°C / min during annealing in step (3) of Example 1 is replaced by the programmed cooling rate in Table 2.
[0124] Table 2: Investigation of programmed cooling rates in the annealing step
[0125] Comparative Example Program cooling rate Comparative Example 11 1.0℃ / min Comparative Example 12 3.0℃ / min Comparative Example 13 4.0℃ / min Comparative Example 14 5.0℃ / min Comparative Example 15 10.0℃ / min
[0126] Comparative Example 16: Prepared by referring to the method of Example 5 in CN115475645A
[0127] The catalyst of Comparative Example 16 was prepared by referring to the method of Example 5 in CN115475645A.
[0128] Example 5: Evaluation Method of Catalysts Prepared by Examples of the Present Invention and Comparative Examples
[0129] 100 mg of the catalyst obtained in the above examples or comparative examples was ground into uniform powder. After sieving, the catalyst powder of 250 μm was selected and loaded into a fixed bed reactor. A mixed gas (propylene: oxygen: nitrogen = 10:5:85 (V / V / V)) was introduced to react. The space velocity was set to 18000 mL / g / h (indicating that the volume of the mixed gas introduced per 1 g of catalyst per hour was 18000 mL), and the temperature was set to 285°C.
[0130] The main parameters for evaluating the performance of the propylene direct epoxidation reaction are: propylene conversion, PO (propylene oxide) selectivity and PO generation rate. The results are shown in Table 1.
[0131] Table 1: Different catalysts and their catalytic performance for direct epoxidation of propylene
[0132]
[0133]
[0134] in conclusion:
[0135] (1) In the preparation method of the present invention, high-purity CO2 is introduced in the precursor prepolymerization step to induce the coordination of metal ions between two-dimensional carrier layers, and the prepared catalyst has excellent propylene conversion rate, PO selectivity and PO generation rate, and its technical effect is significantly improved.
[0136] (2) From the above data, it can be seen that the catalyst with copper diatomic sites has excellent DEP reaction activity, PO selectivity and PO generation rate due to the synergistic effect between the diatoms. The catalyst obtained in Comparative Example 8 is in an O2-containing environment during the prepolymerization stage of catalyst preparation, resulting in the formation of a coordination structure between copper atoms and some oxygen atoms. Compared with the Cu-N coordination of the remaining catalyst active sites, the DEP catalytic activity of the Cu-O coordination is poor. The catalyst obtained in Comparative Example 1 is not in a high-purity CO2 environment during the prepolymerization stage of catalyst preparation, which makes it difficult for copper species to enter the carbon nitride layer and agglomerate to form nanoclusters during the subsequent calcination process. The corresponding XRD characterization shows characteristic diffraction peaks of metallic copper species, so the DEP activity and PO selectivity are poor. The catalyst with only single-atom sites (Comparative Example 2) has almost no DEP catalytic performance because the copper species are relatively dispersed and do not interact with each other.
[0137] (3) Compared with the catalyst of Example 1, the programmed cooling rate during the calcination of Comparative Example 11 is too low, resulting in the catalyst being in a high temperature state for a long time, a large loss of the carrier carbon nitride structure, and migration and agglomeration of the copper active sites, so the PO selectivity is poor; as the cooling rate during the calcination process increases (Comparative Examples 12-15), the surface morphology of the catalyst is prone to change, forming a multilayer structure, which hinders the accessibility of propylene and oxygen in the reaction, so the DEP activity and PO selectivity gradually decrease with the increase of the cooling rate. Therefore, the catalyst obtained by cooling at a programmed cooling rate of 2°C / min has unexpected propylene conversion, PO selectivity and PO formation rate.
[0138] (4) In the preparation method of the catalyst of the present invention, step (1) is preferably carried out under a CO2 atmosphere with a purity higher than 95%, which is beneficial to improving the activity of the obtained catalyst and is beneficial to improving the propylene conversion rate, PO selectivity and PO formation rate of the obtained catalyst in the direct gas-phase epoxidation reaction of propylene.
[0139] (5) In the preparation method of the catalyst of the present invention, it is preferred to carry out the reaction under a CO2 atmosphere with a purity higher than 95%, and to add L-cysteine in step (1). The two have an unexpected synergistic technical effect, which is beneficial to improving the propylene conversion rate, PO selectivity and PO formation rate of the obtained catalyst in the direct gas-phase epoxidation reaction of propylene.
[0140] (6) Compared with other catalysts in the prior art, the catalyst provided by the present invention has unexpectedly excellent propylene conversion, PO selectivity and PO formation rate in the direct gas-phase epoxidation reaction of propylene.
[0141] The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein within the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.
Claims
1. A method for preparing a catalyst, characterized in that: The following steps are involved: (1) in an atmosphere containing carbon dioxide, melamine, a metal salt and a solvent are mixed and stirred for prepolymerization to obtain a suspension A; or in an atmosphere containing carbon dioxide, melamine, a metal salt, an amino acid and a solvent are mixed and stirred for prepolymerization to obtain a suspension A; (2) reacting the suspension A obtained in step (1) at a certain temperature to obtain a solid product, and washing and drying the obtained solid product to obtain a mixture B; (3) Calcination: The mixture B obtained in step (2) is annealed to obtain the catalyst.
2. The preparation method according to claim 1, The amino acid comprises at least one of L-cysteine, glycine and D-phenylalanine, preferably L-cysteine; and / or The stirring speed of step (1) is 500 rpm to 1000 rpm; and / or The stirring time of step (1) is 12h-36h; and / or The stirring in step (1) is carried out at 0°C to 60°C; and / or The carbon dioxide-containing atmosphere is a pure carbon dioxide atmosphere; or The carbon dioxide-containing atmosphere is a mixed gas of carbon dioxide and other gases, wherein the other gases are selected from at least one of nitrogen, argon, oxygen and air; or The atmosphere condition is a mixture of carbon dioxide and other gases, and the volume ratio of the carbon dioxide and other gases is ≥5:1; the other gases are selected from at least one of nitrogen, argon, oxygen or air.
3. The preparation method according to any one of claims 1 to 2, wherein the metal salt is selected from at least one of cupric chloride, cuprous chloride, cupric nitrate, cupric acetate or copper nitride; and / or The solvent is a mixed solvent of water and ethanol; and / or The solvent is a mixed solvent of water and ethanol, and the volume ratio of water to ethanol in the solvent is 1.0:0.8-1.0:1.
5.
4. The preparation method according to any one of claims 1 to 3, wherein the certain temperature in step (2) is 150° C.-240° C.; and / or The reaction time of the reaction in step (2) is 2h-8h; and / or The washing is washing with water and ethanol in sequence; and / or The drying is carried out at 60°C to 80°C; and / or The calcination temperature in step (3) is 300° C. to 650° C.; and / or The calcination time in step (3) is 2h-8h; and / or The heating rate of the calcination in step (3) is 2°C / min to 8°C / min; and / or The calcination in step (3) is carried out in a nitrogen or argon atmosphere; or The calcination in step (3) is carried out in a mixed gas atmosphere of hydrogen and argon; the volume ratio of hydrogen to argon in the mixed gas is 10:90-1:99 or 5:
95.
5. The preparation method according to any one of claims 1 to 4, wherein the annealing is performed by programmed cooling; and / or The programmed cooling is cooling at a rate of 0.5°C / min-5.0°C / min; preferably cooling at a rate of 2.0°C / min; and / or The annealing is annealing to 20°C-30°C.
6. A catalyst prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the catalyst according to claim 6 in catalyzing the gas-phase direct epoxidation reaction of propylene to prepare propylene oxide.
8. A method for preparing propylene oxide, characterized in that: include: In the presence of the catalyst according to claim 6, propylene is subjected to gas phase epoxidation reaction with oxygen to obtain propylene oxide.
9. The preparation method according to claim 8, comprising: In the presence of the catalyst according to claim 6, the propylene and oxygen are diluted with nitrogen and then subjected to gas phase epoxidation reaction to obtain propylene oxide; and / or The volume ratio of propylene to oxygen is 1:1 to 5:1; and / or The volume ratio of propylene to nitrogen is 1:10 to 1:20; and / or In the gas phase epoxidation reaction, 25 mg to 200 mg of the catalyst is added per 1 L of propylene; and / or The reaction temperature of the gas phase epoxidation reaction is 200°C to 350°C; and / or The particle size of the catalyst is ≤300 μm or ≤250 μm, preferably 250 μm.
10. The preparation method according to claim 8, comprising: The propylene and oxygen are subjected to gas phase epoxidation reaction in a fixed bed reactor filled with the catalyst according to claim 6 with nitrogen as carrier gas to obtain propylene oxide; and / or The volume ratio of propylene to oxygen is 1:1 to 5:1; and / or The volume ratio of propylene to nitrogen is 1:10 to 1:20; and / or The space velocity of the gas phase epoxidation reaction is 6000ml / g / h-40000ml / g / h; and / or The reaction temperature of the gas phase epoxidation reaction is 200°C to 350°C; and / or The particle size of the catalyst is ≤300 μm or ≤250 μm, preferably 250 μm.
Citation Information
Patent Citations
Oxidation catalyst as well as preparation method and application thereof
CN115475645A
Cited By
Amino acid modified copper-based catalyst as well as preparation method and application thereof
CN121250451A